Speech Acts in Exploring Glamour, Violence, and Vulnerability in Lana Del Rey's Album Ultraviolence: Pragmatics Study - Vinsentius Dhanumbara Sindhuaji; Ervina CM Simatupang (JURNALISTRENDI : JURNAL LINGUISTIK, SASTRA, DAN PENDIDIKAN, 2024)
This study explored the use of speech acts in Lana Del Rey’s album Ultraviolence, with a particular focus on how the themes of glamour, violence, and vulnerability are conveyed through the album’s lyrics. By using speech act theory and pragmatics, the research analyzed five types of speech acts; which were assertive, expressive, directive, commissive, and declarative; across selected songs. The findings reveal that assertive speech acts dominate, accounting for approximately 40% of the total instances, and they primarily assert the complex emotional dynamics in relationships, especially concerning violence and vulnerability. Expressive speech acts resulted 25%, reflecting emotional openness and fragility. Directive acts, representing about 15%, critique societal expectations, while commissive speech acts contributed 10%, expressing commitment and submission. Declarative speech acts, which focus on identity and glamour, comprise the remaining 10%. Through these speech acts, Del Rey critiques traditional ideals of romance and femininity, blending personal vulnerability with a glamorous yet dark portrayal of relationships. This research underscores the power of song lyrics as a medium for linguistic and cultural expression, offering a deeper understanding of how language can construct, challenge, and reflect societal norms and emotional experiences.